2011
DOI: 10.1155/2011/890258
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of Multilink Manipulators Based on Timoshenko Beam Theory

Abstract: Timoshenko's theory is adopted in order to accurately describe the freely vibrating dynamics of a multilink flexible manipulator. It is herein presented an analytical modelling strategy that extends previous works through a more refined model which accounts for elastic complicating effects along with lumped inertial loads which are typically mounted on joints of manipulators; in this regard, more accurate results are provided. The eigenproblem is presented from an analytical point of view through a matrix form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Matrix representation for joint and deflection motion has been used and deflection transformations have been expressed in terms of summation of mode shapes with a further comparison of the presented formulation with the earlier reported rigid link cases. Timoshenko beam model has been adopted by [8] to accurately model the dynamics of freely vibrating multi-link flexible manipulator incorporating the elastically complicated effects along with the inertia loads typically mounted on the joints of the manipulator. The influences of the slenderness ratio and the angular configuration of the manipulator on the natural frequencies have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix representation for joint and deflection motion has been used and deflection transformations have been expressed in terms of summation of mode shapes with a further comparison of the presented formulation with the earlier reported rigid link cases. Timoshenko beam model has been adopted by [8] to accurately model the dynamics of freely vibrating multi-link flexible manipulator incorporating the elastically complicated effects along with the inertia loads typically mounted on the joints of the manipulator. The influences of the slenderness ratio and the angular configuration of the manipulator on the natural frequencies have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Patel and George presented survey on [1] parallel manipulators applications concluded that a continued and incessant effort by researchers will lead to an increased capability and effectiveness of various parallel robotics et al [2] presented a novel approach of workspace modeling with Euler parameters is proposed for a special class of spherical parallel manipulators with symmetrical structure [3] presented a multi-objective optimization problem is formulated to optimize the structural and geometric parameters of the spherical parallel manipulator. Castri and Messina [4] described the freely vibrating dynamics of multi-link flexible manipulator adopting Timoshenko's theory. Rong et al [5] reported a stiffness and modal analysis of precision parallel manipulator with flexure hinges.…”
Section: Introductionmentioning
confidence: 99%